O papel da política de prevenção à criminalidade para o alcance da segurança cidadã: estudo de caso dos programas de base local do governo do estado de Minas Gerais - Miranda, Débora Silva de (2015)
This dissertation deals with the contribution of the Social Crime Prevention Programs of the State Government of Minas Gerais executed on local basis, the "Fica Vivo!" and "Mediação de Conflitos" programs, in search for the citizen security in their living areas. Based on the principles proposed by international organizations -- in special UNDP, OAS, IDB -- the "citizen security" paradigm, it was observed that the concept embraces the building of higher levels of citizenship, focusing on the protection of individuals and social groups rights, through democratic models of prevention and repression of crime and violence. Historical review of the public safety policy in Brazil revealed its use for the benefit of private and local interests as well as a mechanism of social control and maintenance of the status quo. Thus, the issue of public safety struggled to get into the political and social agenda, even after the democratic transition, although democratization has fostered the opening of several social policies. The citizen security concept was only consolidated in Brazil within the 1st "National Conference on Public Safety", in 2009. The citizen security perspective is associated with a new paradigm of crime prevention, which led to the search for theoretical evolution and the evaluation of its preventive strategies. Based on fieldwork and interviews we found that "Fica Vivo!" and "Mediação de Conflitos", can be understood as developmental strategies and community crime prevention programs. It was noticed the adequacy of their logical frameworks to the citizen security paradigm, and we observed the necessity of supporting a network to the implementation of their actions and the development of their contribution to the achievement of citizen security in the communities in which they settle. Thus, theoretical discussion on the concept of policy networks supported the analysis of the development of programs with field research carried out in one "Crime Prevention Centre" of the metropolitan region of Belo Horizonte. Several difficulties of the programs were observed in operating in an integrated and coordinated way with state and local organizations, although there are initiatives of networking. In addition, community representatives and local organizations are not motivated to participate and coordinate with the programs in order to search for improvements in the community.